Crystal structure, energetics, and phase stability of strengthening precipitates in Mg alloys: A first-principles study. (1st October 2018) - Wang, Dongshu; Amsler, Maximilian; Hegde, Vinay I.; Saal, James E.; Issa, Ahmed; Zhou, Bi-Cheng; Zeng, Xiaoqin; Wolverton, Chris
Abstract: Magnesium alloys have attracted increasing interest due to their potential use as light-weight structural materials but their application is limited by their low strength compared to conventional alloys. Age hardening is commonly employed to form strengthening precipitates in such alloys, which impedes the motion of dislocations, and leads to improved strength. However, the exact composition, crystal structure, and energetics of many of these strengthening precipitates are either unknown or not clearly resolved, making the precise engineering and design of such alloys difficult. Toward this end, we use first-principles density functional theory calculations to elucidate the crystal structures and energetics of a very large set of precipitates in magnesium alloys. For cases where the precipitate crystal structure is not known, we comprehensively search over decorations of many prototype structures, including hcp superstructures, and in addition, perform global structural optimization using the Minima Hopping Method to predict suitable crystal structures. For all the strengthening precipitates, we calculate the formation energies, construct the respective zero temperature convex hulls, and analyze their stabilities. We show that the bulk formation energies per solute atom (essentially, the solute chemical potentials) decrease along the observed sequences of precipitation, validating our calculations in Mg-Nd, Gd, Y, Y-Nd, Nd-Zn, Gd-Zn, Y-Zn, Al, Zn, Sn, Al-Ca, Ca-Zn alloy systems. In addition, we construct a monolayer model for the Guinier-Preston zones (GP zones) observed in the Mg-Nd-Zn system during early stages of age hardening, and thereby explain the formation of the γ '' (Mg5 (Nd, Zn)) phase from the GP zones, as observed in experiments. Graphical abstract: Image 1